Principals’ Records-Keeping Practices and School Effectiveness in Ilorin Metropolis Secondary Schools - Olaifa, Adeseko Sunday; Fagbola, Simbiat Mojibola; Ayoku, Oba Baba; Sagaya, Abiodun Amudalatu; Hassan, Solawat Ajibola; Abolarin, Taibat Joke (Institute For Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The research focuses on the record-keeping practices of principals in public secondary schools in Ilorin metropolis, Kwara State, Nigeria. Two research questions and one research hypothesis were raised to guide the study. A descriptive survey research design was employed, allowing for self-reporting of information without manipulating variables. The sample included 121 principals and 155 vice principals from four Local Government Areas. The research instrument was a structured questionnaire,